Tiny Circular Economy Practices in the Cagayan Valley Region, Philippines: A Case Study of Native Chicken Farmers - Liangco, N. C.; Guntoro, B.; Haryadi, F. T.; A’yun, A. Q.; Qui, N. H. (Tropical Animal Science Journal, 2025)
This study investigated the adoption of tiny circular economy (TCE) practices among native chicken farmers in the Cagayan Valley region of the Philippines, examining the influence of farmers’ perceptions and motivations on TCE practices. Using a purposive sample of 400 farmers, the research explored how farmers’ perceptions of support from government and non-government organizations, alongside their motivations (existence, relatedness, and growth), impact the implementation of TCE in native chicken production. Data were analyzed by using multiple linear regression to quantify these effects. The findings reveal that a significant majority (68.25%) of farmers in the region have adopted sustainable TCE practices, which form a circular system encompassing food production, consumption, and waste management. These practices include utilizing leftover food as chicken feed, allowing chickens to forage naturally, employing organic fertilizers derived from animal manure and plant waste, and selling chickens and eggs for income. Moreover, the results indicated that farmers’ perception of the support from government and NGOs had a significant impact on TCE adoption (p<0.05), whereas motivation exerted a stronger influence (p<0.01). Additionally, TCE adoption leads to reduced production costs (particularly feed and fertilizer), increased income from premium-priced organic products, waste reduction, and overall environmental sustainability. The findings suggest that farmers’ perception and motivation have a positive influence on the adoption of smallholder TCE practices, contributing to reducing production costs, increasing income, and promoting sustainable development in native chicken farming.